Effect of container size and types on the root phenotypic characters of Capsicum - Raviteja, M S V; Laxman, R H; Rashmi, K; Kannan, S; Namratha, M R; Madhavi Reddy, K (Journal of Horticultural Sciences, 2021)
Capsicum genus comprised of several cultivars is considered as an important spice crop worldwide. Roots play a vital role in a plant to mine water from the deeper layers of the soil. Although, characterisation for root traits have been made using different containers in many crops, such efforts for phenotyping root characteristics in Capsicum species are limited. Therefore, the experiment was initiated to find out the influence of container size on root characteristics and also to identify the appropriate container for high throughput phenotyping of Capsicum species for desirable root characteristics. Nine genotypes belonging to different Capsicum spp. were grown in three types of containers having different dimensions. Among the three types of containers, the bucket type container with dimension of 32 cm height 30 cm diameter with 23 kg soil media capacity was most suitable for phenotyping root characteristics compared to PVC pipe and pot type. Subsequently, 18 genotypes were phenotyped for plant growth and root characteristics in the bucket type container. The genotypes IHR 4517, IHR 3529, IHR 4501, IHR 4550, IHR 4491 and IHR 3241 with better root characteristics were identified.